Culturally Sensitive Approaches to Research on Child Development and Family Practices in First Peoples Communities - McShane, Kelly E.; Hastings, Paul D. (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2004)
This paper focuses on highlighting some of the concerns that need to be addressed in conducting psychological research with First Peoples children and families. The extensive literature on healthy child development and family practices in Caucasian families is contrasted with the limited perspective on First Peoples families. We suggest that this is, in part, due to an unnecessary focus on problem behaviours of children from First Peoples communities. We contend that it is imperative for developmental psychologists to adopt a new perspective, by acknowledging the strengths and competencies of First Peoples families, and using more culturally-sensitive approaches to working with First Peoples.